A judicialização da megapolítica no Supremo Tribunal Federal e suas implicações para o avanço da desdemocratização no Brasil - Finger, Anays Martins (2022)
This work aimed to demonstrate how the judicialization of Megapolitics, based on the jurisdictional role of the Federal Supreme Court in the judgment of the ADPF 378 case, during the impeachment of Dilma Rousseff, contributed to the advance of dedemocratization in Brazil. The analysis of this theme was driven by the leading role that the Court assumed in the political arena, a fact that was consolidated with the delineation of the work of the Operation Car Wash. Based on this, the following research problem was formulated, to be answered in this dissertation: in what ways did the Federal Supreme Court, with the decision issued in the ADPF 378 case, during the impeachment of Dilma Rousseff, contributed to the dedemocratization process in course in the country? To answer this question, as a research methodology, the inductive approach method was used, with content analysis, since the research starts from the study of a specific case, ADPF 378, to answer the research problem, globally considered, that deals with conceiving the judicialization of Megapolitics as a factor that contributed to the crisis of Brazilian democracy. The procedure method used was the bibliographic, considering that the research was elaborated from books, periodicals and scientific articles of the work's base theory and of the other authors that make up the theorical framework. Furthermore, the use of the bibliographic procedure also proved to be relevant to the proposal of analysis of the Federal Supreme Court case law. Research techniques such as the elaboration of annotations and expanded abstracts, as well as the search for judicial rulings on the Supreme Court's website, were also part of this process. The theorical and legal basis of this work relied on the important arguments of Ran Hirschl, Charles Tilly and Byung-Chul Han. At last, it was concluded that the judicialization of Megapolitics, parting from the ruling of the Federal Supreme Court in the ADPF 378 case, contributed in several ways to the advance of dedemocratization in Brazil. Entering the field of pure politics, regulating the dictates of an essentially political process such as the impeachment, the Court ended up defining the course that the Brazilian political conjuncture would follow from then on, which also created favorable conditions for the election of Jair Bolsonaro for the presidency and the respective consolidation of the crisis of representation that the country is a victim of. Despite the fact that a strong, autonomous and independent Judiciary is an indispensable condition for democracy, jurisdictional courts should not enter other branches specific matters, such as in the case of impeachment, in which the determination of procedural rules is an attribution, per excellence, of the Legislative branch.